The correlations between serum bone biomarkers and those related to metabolic and hormonal profile, low-grade inflammation and redox balance, in lean and overweight PCOS adolescent girls - Mizgier, Małgorzata; Sansoni, Veronica; Więckowska, Barbara; Jarząbek-Bielecka, Grażyna; Formanowicz, Dorota; Kędzia, Witold; Banfi, Giuseppe; Lombardi, Giovanni (Frontiers in Nutrition, 2025)
IntroductionIt has been proven that polycystic ovary syndrome (PCOS) is associated with reduced bone mineral density (BMD) and impaired bone metabolism. However, to the best of our knowledge, neither the relationship between indices of bone turnover in adolescent girls was examined, nor were lean and overweight PCOS young females compared in this regard, which were the aims of our study.MethodsThirty-nine PCOS subjects, aged 14–18 years, were assigned to one of the two groups: Ov/Ob (overweight/obese group, n = 14) and lean (non-overweight/non-obese group, n = 25). Fasting blood samples were collected to assess bone turnover, inflammation, oxidative stress, and hormonal markers. Basic anthropometric and biochemical data were also obtained.ResultsIn Ov/Ob young females, concentrations of bone turnover markers, GlaOC, GluOC, and CTX-I (selective bone resorption marker), were lower than in lean PCOSs. However, this difference was statistically significant only for GlaOC. The serum activity of bone alkaline phosphatase (BAP), a bone formation index, tended to be higher in the Ov/Ob than in lean PCOS patients, although not significantly. Additionally, we observed an inverse association between low-grade inflammation, oxidative stress, androgen levels (total testosterone and/or DHEA-S), and BAP and/or GlaOC in both lean and Ov/Ob groups, together with a positive association between Total Antioxidant Capacity (TAC) and BAP. Moreover, fasting glucose, insulin, and HOMA-IR positively correlated with GluOC and BAP in lean girls.DiscussionOur outcomes suggest a potential negative interaction between bone markers and immune-hormonal abnormalities featuring lean and Ov/Ob adolescent PCOS girls. Moreover, these findings suggest a positive interaction between bone metabolism and total antioxidant capacity, and insulin and glucose management exists in the body. Although these findings require further investigation, all possible preventive measures should be taken to lower inflammation, oxidative stress, and androgen levels, also keeping bone well-being/homeostasis in mind.